MEMAKSIMALKAN HASIL PADI SALIBU MENGGUNAKAN PUPUK UREA DAN PUPUK NPK - Paiman Paiman; Sukhemi; Nendra Mursetya Somasih Dwipa (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
The salibu rice is a modification from ratoon rice system. The application of inorganic fertilizers can increase the salibu rice yield. This study aims to know the optimum dose of urea and NPK Phonska fertilizers to maximize the salibu rice yield. This experiment was a pot experiment arranged in a completely randomized design (CRD) factorial with three replications. The first factor was the dose of urea fertilizer consisted of three levels, namely: 100, 200, and 300 kg ha-1. The second factor was the dose of NPK Phonska fertilizer which consisted of three levels, namely: 100, 200, and 300 kg ha-1. In the study, added one treatment as a control (without treatment). The results showed that urea and NPK Phonska could be increased leaf greenery, tillers number, canopy dry weight, and dry weight of grain per hectare. The optimum dose of urea fertilizer was found at 317.6 kg ha-1 and yielded a maximum grain dry weight of 4.96 tons ha-1, and the optimum dose of Phonska NPK fertilizer was obtained at 231.7 kg ha-1 and gave the maximum grain dry weight of 4.71 tons ha-1. The findings of the study indicate that the interval application of urea fertilizer has not reached the optimum dose, while the NPK Phonska fertilizer is found at 231.7 kg ha-1. In future research suggest that the application of urea fertilizer can be increased with doses higher than 300 kg ha-1 in the salibu rice cultivation.